Study of the mineral composition of Lychnis coronaria raw materials - Polishchuk , Yuliia; Burda, Nadiia (Annals of Mechnikov's Institute, 2022)
Introduction. Lychnis coronaria (L.) Murray ex Desr. is a perennial herbaceous plant in the Caryophyllaceae family. The raw material of Lychnis coronaria is unofficial, but it is used in traditional medicine in many countries, including Ayurvedic, as a means of wound healing, anti-inflammatory activity in skin diseases, liver, hemorrhoids and more. In addition, the above activity is noted by foreign scientists working on the study of Lychnis coronaria. Regarding the study of the chemical composition of the plant, the compounds of phenolic and terpene nature, in particular steroids, which may cause a pronounced anti-inflammatory activity of the plant, are being studied to a greater extent. However, current information on chemical composition needs to be deepened. It is known that minerals also show pharmacological activity, it is important to study the mineral composition of Lychnis coronaria raw material. Information on the manifestation of anti-inflammatory activity of minerals is confirmed by scientific research. Therefore, the aim of the work was to determine the mineral composition of Lychnis coronaria raw material. Materials and methods. Herb, leaves, flowers, stems, roots and seeds of Lychnis coronaria were used for the study. Herb, leaves, flowers and stems were harvested during the flowering period; seeds - during fruiting; roots - after the extinction of the aboveground part during 2020-2021 in the Kharkiv region. Before analysis the crude samples pretreated with diluted sulfuric acid were carbonized in a muffle furnace (temperature max. 500oC). Samples were evaporated from graphite electrode craters in AC arc discharge at 16 A current and 60 sec exposure. Spectra were obtained and registered at DFS-8 spectrograph with diffraction grating of 600 grooves/mm and three-lens slit illumination system. Specter photography terms: AC arc current 16 A, ignition phase 60oC, ignition pulse frequency 100 discharges per second, analytical gap 2 mm; spectrograph slit width 0,015 mm; exposure 60 sec. Specters were photographed at 230-330 nm range. Photo plates were developed, dried, then the following lines (in nm) were photomeasured in spectra of samples and graduated specimens as well as their background. For each element we calculated from photometry results the differences in blackening of lines and background (S=Sl+b – Sb) for spectra of samples (Se) and of calibration specimens (Scs). Then we built the calibration plot in such coordinates: mean value of lines and background blackening difference (Scs) – calibration specimens element content logarithm (lg C), where C is expressed in per cent relative to base. From this plot we found an element content in ash (a, %). The element content in plant material (x, %) we found by formula: ,where m – ash mass, g; M – crude material mass, g; a – element content in ash, %. In analysis we considered the bottom limits of impurities content which were for Cu – ; for Co, Cr, Mo, Mn, V – ; for Ag, Ga, Ge, Ni, Pb, Sn, Ti – ; for Sr, Zn – %. Research results. As a result of the study, the presence of 19 mineral elements in all types of studied raw materials was established, and their quantitative content was determined. The total content of mineral elements dominated in the seeds of Lychnis coronaria (11213.01 mg / 100 g). In addition, it should be noted that a significant content of elements was observed in the stems and roots of the studied plant - 7647.78 mg / 100 g and 7609.64 mg / 100 g, respectively. The least accumulation of certain mineral elements occurred in the flowers and leaves of Lychnis coronaria. It should be noted that among the mineral elements in all studied raw materials, potassium predominated. In addition, calcium, magnesium, phosphorus and silicon had a fairly high content in the studied raw materials. Thus, it can be assumed that the high content of the above mineral elements may play a role in the manifestation of anti-inflammatory activity of Lychnis coronaria raw material. Conclusions. Thus, the results obtained on the study of the mineral composition of the raw material of Lychnis coronaria deepen the knowledge about the chemical composition of this plant. In addition, these data can be used in the further standardization of the studied raw materials, as well as in the study of pharmacological activity. Keywords: Lychnis coronaria (L.) Murray ex Desr., mineral composition. DOI: 10.5281/zenodo.6634860